I'm stuck on the following problem.

Use the fact that $$\sum_{\substack{p\le x \\ p\,\text{prime}}}\frac{\log p}{p}=\log (x)+O(1)$$ to show that $$\sum_{\substack{n\le x \\ n\in\mathbb{N}}}\frac{\Lambda(n)}{n}=\log (x)+O(1),$$ where $\Lambda$ is the von Mangoldt function.

It looks like it should be easy. Please help; hints are preferred.

My main set back is figuring out what to do with the powers of primes. Here's what I've got so far.

We have $$O(1)=\sum_{\substack{p\le x \\ p\,\text{prime}}}\frac{\log (p)}{p}-\log (x)$$ so there exists a $\lambda>0$ s.t. for any $\varepsilon>0$ there exists $M_{\varepsilon}>0$ s.t. if $x>M_{\varepsilon}$ then $$\left\lvert\sum_{\substack{p\le x \\ p\,\text{prime}}}\frac{\log (p)}{p}-\log (x)\right\rvert\le\lambda\lvert 1\rvert =\lambda.$$

So let $\varepsilon>0$. Now, by definition of $\Lambda$, we have (for $x>M_{\varepsilon}$) that, with $P(x)$ as "$p^k\le x, p\, \text{prime}, k\in\mathbb{N}\backslash\{1\}$,"

$$ \begin{align} \left\lvert\sum_{\substack{p^k\le x \\ p\,\text{prime} \\ k\in\mathbb{N}}} \frac{\log (p)}{p^k}-\log (x)\right\rvert &\le \left\lvert\sum_{\substack{p\le x \\ p\,\text{prime}}} \frac{\log (p)}{p}-\log (x)\right\rvert +\left\lvert\sum_{P(x)}\frac{\log (p)}{p^k}\right\rvert. \\ &\le \lambda + \left\lvert\sum_{P(x)}\frac{\log (p)}{p^k}\right\rvert \\ &= \lambda + \sum_{\substack{p^2\le x \\ p\,\text{prime}}} \frac{\log p}{p^2}+\sum_{\substack{p^3\le x \\ p\,\text{prime}}} \frac{\log p}{p^3}+\dots \\ &= \lambda + \sum_{k=2}^\infty\underbrace{\sum_{\substack{p^k\le x \\ p\,\text{prime}}} \frac{\log p}{p^k}}_{\text{Each of these is less than }\lambda.}\tag{1} \\ &\le\sum_{k\in\mathbb{N}}\lambda. \end{align} $$

But there are infinitely many terms in that series of $\lambda$s, so that bound is too crude (of course). The terms in $(1)$ are each bounded by some (minimal) constant $\sigma_{k, x}$ though so I just need to show that $$\sum_{k=2}^\infty\sigma_{k, x}<\infty$$ if at all possible :/

My aim is to bound it all by a constant.

I've tried other things too but - believe it or not - this seems like my best shot.

  • $\begingroup$ This was the closest thing I could find: math.stackexchange.com/questions/33980/… $\endgroup$
    – Shaun
    Feb 10, 2014 at 20:33
  • $\begingroup$ I spent time on this crap. It's an instance of when one hopes asking the question helps one answer it. $\endgroup$
    – Shaun
    Feb 10, 2014 at 20:40
  • 2
    $\begingroup$ Have you tried applying Abel's identity? For an example (and a reference to Abel's identity) see here: math.stackexchange.com/a/12588/1102 $\endgroup$
    – Aryabhata
    Feb 10, 2014 at 21:08
  • 1
    $\begingroup$ Just pointing out that you introduced a quantity $\epsilon$ that doesn't get used. You can just directly say: there exists $\lambda$ and $M$ such that for $x>M$, your second displayed equation holds. $\endgroup$ Feb 11, 2014 at 7:07
  • 1
    $\begingroup$ Yep, there's never a need to introduce a quantity you never use. (Math is about verifying truths, not placating an epsilon overlord!) $\endgroup$ Feb 11, 2014 at 18:54

1 Answer 1


In the written-out term you can bracket the $\log{p}$'s and you get $$S=\sum\limits_{n\leq x}\frac{\Lambda(n)}{n}=\sum\limits_{p\leq x}\log{p}\left(\sum\limits_{p^i\leq x}\frac{1}{p^i}\right)$$ The term in the bracket is bounded by $$\frac{1}{1-\frac{1}{p}}-1=\frac{1}{p-1}$$ So $$S\leq\sum\limits_{p\leq x}\frac{\log p}{p-1}=\sum\limits_{p\leq x}\frac{\log p}{p}+\sum\limits_{p\leq x}\frac{\log p}{p^2-p}=\log x + O(1)$$ since the last sum converges.

Furthermore, because we add terms to it if using the von Mangoldt function instead of the logs of primes, we obtain $$\log x+O(1)=\sum\limits_{p\leq x}\frac{\log p}{p}\leq S$$ and we see that $S=\log x + O(1)$.

I'm not sure if the last step is correct, because I'm not used to the Big O notation, so please reply if this is invalid.

  • 1
    $\begingroup$ The last is a little abuse-of-notationish, but that's common with big-Oh notation. You could write $$0 \leqslant S - \sum_{p\leqslant x} \frac{\log p}{p} \leqslant C := \sum_{p} \frac{\log p}{p(p-1)} < \infty.$$ $\endgroup$ Feb 10, 2014 at 22:20
  • $\begingroup$ Thank you. I wasn't sure about that bound and the convergence of the second sum at first but I think it checks out. And thank you, @DanielFischer, for the clarification :) $\endgroup$
    – Shaun
    Feb 11, 2014 at 16:41

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.